Does deep inspiration breath-hold prolong life? Individual risk estimates of ischaemic heart disease after breast cancer radiotherapy - Simonetto, Cristoforo; Eidemüller, Markus; Gaasch, Aurélie; Pazos, Montserrat; Schönecker, Stephan; Reitz, Daniel; Kääb, Stefan; Braun, Michael; Harbeck, Nadia; Niyazi, Maximilian; Belka, Claus; Corradini, Stefanie (Radiotherapy and Oncology, 2019)
Purpose: Aim of the current comparative modelling study was to estimate the individual radiation-induced risk for death of ischaemic heart disease (IHD) under free breathing (FB) and deep inspiration breath-hold (DIBH) in a real-world population. Materials and methods: Eighty-nine patients with left-sided early breast cancer were enrolled in the prospective SAVE-HEART study. For each patient three-dimensional conformal treatment plans were created in FB and DIBH and corresponding radiation-induced risks of IHD mortality were estimated based on expected survival, individual IHD risk factors and the relative radiation-induced risk. Results: With the use of DIBH, mean heart doses were reduced by 35% (interquartile range: 23–46%) as compared to FB. Mean expected years of life lost (YLL) due to radiation-induced IHD mortality were 0.11 years in FB, and 0.07 years in DIBH. YLL were remarkably independent of age at treatment in patients with a favourable tumour prognosis. DIBH led to more pronounced reductions in YLL in patients with high baseline risk (0.08 years for upper vs 0.02 years for lower quartile), with favourable tumour prognosis (0.05 years for patients without vs 0.02 years for those with lymph-node involvement), and in patients with high mean heart doses in FB (0.09 years for doses >3 Gy vs 0.02 years for doses <1.5 Gy). Conclusion: Ideally, the DIBH technique should be offered to all patients with left-sided breast cancer. However, highest benefits are expected for patients with a favourable tumour prognosis, high mean heart dose or high baseline IHD risk, independent of their age.
CRIS-Team Scopus Importer:2025-10-13
Keywords: 3-D conformal radiotherapy; Breast cancer; Deep inspiration breath-hold; Ischaemic heart disease; Risk factors; Risk model